Adiponectin Action: A Combination of Endocrine and Autocrine/Paracrine Effects - Sweeney, Gary (Frontiers in Endocrinology, 2011)
The widespread physiological actions of adiponectin have now been well characterized as clinical studies and works in animal models have established strong correlations between circulating adiponectin level and various disease-related outcomes. Thus, conventional thinking attributes many of adiponectin’s beneficial effects to endocrine actions of adipose-derived adiponectin. However, it is now clear that several tissues can themselves produce adiponectin and there is growing evidence that locally produced adiponectin can mediate functionally important autocrine or paracrine effects. In this review article we discuss regulation of adiponectin production, its mechanism of action via receptor isoforms and signaling pathways, and its principal physiological effects (i.e., metabolic and cardiovascular). The role of endocrine actions of adiponectin and changes in local production of adiponectin or its receptors in whole body physiology is discussed.